Benign Smooth Muscle Tumors (Leiomyomas) of Deep Somatic Soft Tissue. (9th September 2018) - McCarthy, Aoife J.; Chetty, Runjan
Abstract : Leiomyomas of deep soft tissue are extremely rare and should only be diagnosed following adherence to stringent histological criteria, namely, the absence of nuclear atypia and of coagulative tumor necrosis. Whether extremely low counts of, or even any, mitotic activity are acceptable when making a diagnosis of leiomyoma in deep soft tissue sites is controversial. The morphology and immunophenotype of smooth muscle tumors in deep soft tissue are similar to their counterparts irrespective of topography. It is interesting to note that leiomyomas of deep soft tissue (extremity and retroperitoneum) are often hyalinized/sclerosed and calcified. However, the prediction of their behavior and correct codification is dependent on thorough, meticulous search for mitoses and necrosis. Leiomyomas of deep soft tissue in the extremity should be devoid of mitoses and "significant" cytological atypia. An occasional larger, slightly pleomorphic cell in the midst of bland spindle cells, can be regarded as insignificant atypia. If any mitotic activity and several atypical cells are encountered in smooth muscle tumors of deep soft tissue of the extremity, it would be prudent to invoke the appellation of smooth muscle tumor of uncertain malignant potential and advocate wide local excision and follow-up.